Glufosinate Rate and Timing for Control of Glyphosate-Resistant Rhizomatous Johnsongrass (Sorghum halepense) in Glufosinate-Resistant Soybean - Randall L. Landry; Daniel O. Stephenson; Brandi C. Woolam (International Journal of Agronomy)
Field studies were conducted over a three-year period (2011, 2012, and 2013) in Louisiana to evaluate the effect of glufosinate rate and timing on glyphosate-resistant (GR) rhizomatous johnsongrass control in glufosinate-resistant soybean. Treatments included glufosinate (0.5, 0.6, or 0.7 kg ai ha−1) applied alone POST1 (46 cm tall johnsongrass) and sequentially 3 (POST2) or 4 (POST3) wk after POST1 at 0.5 or 0.6 kg ha−1. Glufosinate (0.7 kg ha−1) applied POST1 controlled johnsongrass 77% at soybean harvest. Averaged across sequential application rate, delaying the sequential application from POST2 to POST3 increased control from 65 to 78% at harvest. Increasing sequential application rate from 0.5 to 0.6 kg ha−1 reduced johnsongrass heights 15% at harvest. Furthermore, delaying the sequential application from POST2 to POST3 reduced GR rhizomatous johnsongrass heights to 63% of the nontreated at harvest. Soybean yields were maximized following the POST1 application of glufosinate at 0.7 kg ha−1 (2670 kg ha−1) and by applying 0.6 kg ha−1 of glufosinate sequentially (2620 kg ha−1), regardless of sequential application timing. Maximum control and soybean yield were observed following glufosinate POST1 at 0.7 kg ha−1 followed by 0.6 kg ha−1 at POST3. This data indicates that glufosinate is an option for management of GR rhizomatous johnsongrass.